A comprehensive review on nutritional composition, health benefits, and industrial applications of Jackfruit Seeds - Simran Dhani; Hamid; Nomali Ziphorah Ngobese; Sunny Sharma; Amit K. Jaiswal (Journal of Agriculture and Food Research)
Jackfruit (Artocarpus heterophyllus Lam.) is one of the undervalued fruits that is rich in many nutrients not only in the edible parts but also in generated waste such as the seed and peel. Seeds of jackfruit are usually considered as waste (15 %) but are rich in protein, starch as well as various bioactive compounds. Among the bioactive components, phenolics like catechin, ferulic acid, epicatechin, rutin, and gallic acid, are a few which possess many health-promoting properties. These bioactive compounds hold high antioxidant capacity and various pharmacological properties which lower the risk of various diseases by reducing free radical generation. Fortification with jackfruit seed flour will help in increasing the protein content of the developed product besides helping in the waste valorisation. Furthermore, starch extracted from discarded jackfruit seeds can be utilized as thickeners, gelling agents and fillers meanwhile its potential applications in the pharmaceutical industry. So this review emphasizes the nutritional composition, antinutritional factors and health benefits of jackfruit with related applications for product formulations. In terms of nutritional components, we place a focus on the exploration of extraction techniques of starch and its functional properties in relation to industrial applications. Therefore, this review aims to consolidate the findings and create a comprehensive account of the potential of jackfruit seeds for the food industry.